Copyright Protection in National Legislation - Cristina Dinu (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law, 2024)
Copyright, as an independent branch of intellectual property law, is of particular importance in today's society that relies more and more on content, especially on social media networks (pictures, images, songs, videos). Copying them, and using them requires a good knowledge of the notion of copyright, and of the regulation at the European Union level but also at the national level, it also requires a good knowledge of the mechanisms that can be used to protect these copyrights.